Tradisi Aruh Adat Buntang Mamali Mati Suku Dayak Deah di Desa Kambang Kuning Kecamatan Haruai Kabupaten Tabalong Kalimantan Selatan - Farahdiyana, Hani; Effendi, Rusdi; Mansyur, Mansyur (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The Aruh Adat Buntang Mamali Mati tradition, Kambang Kuning Village, Haruai District, Tabalong Regency is a sacred ceremony tradition that is still carried out from generation to generation from the ancestors of the Dayak Deah tribe. This ceremony is carried out with the aim of delivering the spirits of ancestors who have died to the next life.The method used in this research is the historical method, which consists of Heuristics, Criticism, Interpretation, and Historiography. The Heuristic stage is the stage of data collection of primary data and secondary data. While the sources obtained consist of oral sources obtained from interviews, written sources obtained from theses, theses, journals and books, sources of objects obtained when researchers saw the equipment for the implementation of the Buntang Mamali Mati ceremony. The criticism stage is internal criticism and external criticism. Interpretation stage, and Historiography or writing stage.The results of this study indicate that the Aruh Customary Buntang Mamali Mati Tradition of Dayak Deah Ethnicity in Kambang Kuning Village, Haruai District, Tabalong Regency, South Kalimantan must be carried out by people who still adhere to the Kaharingan or Hindu Kaharingan beliefs whose families die. This is due to the belief of the Dayak Deah tribe that the spirit that has died will go to the next life so it is necessary to hold the Aruh Buntang Mamali Mati ceremony to provide for the spirit in the next life.